MICROFINANCE FOR ECONOMIC AND POLITICAL EMPOWERMENT OF WOMEN IN INDIA: A STUDY WITH FOCUS ON „KUDUMBASHREE‟ EXPERIENCE IN KERALA - Manoj P K
Microfinance is fast emerging as a tool for poverty alleviation and socio-economic development of the poor, particularly in the developing countries including India. Equally important is the role of microfinance in bringing about gender equity through political as well as economic empowerment of women. This paper looks into the international experiences in respect of the efficacy of microfinance initiatives in empowering women, the Indian scenario in this regard, the specific case of ‘Kudumbashree’ project in Kerala state in Indian union, and finally suggests a few strategies for more effective functioning microfinance initiatives for women empowerment.